Finite Size Effects in Antiferromagnetic Highly Strained BiFeO 3 Multiferroic Films - Sando, Daniel; Appert, Florian; Paull, Oliver; Yasui, Shintaro; Bessas, Dimitrios; Findiki, Abdeslem; Carrétéro, Cécile; Garcia, Vincent; Dkhil, Brahim; Barthelemy, Agnès; Bibes, Manuel; Juraszek, Jean; et al. (Advanced Physics Research, 2024)
Epitaxially strain‐engineered tetragonal (T)‐like BiFeO 3 (BFO) is a multiferroic material with unique crystallographic and physical properties compared to its bulk rhombohedral parent. While the effect of this structural change on ferroelectric properties is understood, the influence on correlated antiferromagnetic (AFM) properties, especially with reduced film thickness, is less clear. Here, the AFM behavior of T‐like BFO films 9–58 nm thick on LaAlO 3 (001) substrates fabricated by pulsed laser deposition was studied using conversion electron Mössbauer spectroscopy and X‐ray diffraction. The key findings include: i) Ultrathin T‐like BFO films (<10 nm) show a decoupling of magnetic and structural transitions, with the polar vector tilted 32 degrees from [001] in 9–13 nm films. ii) Films thinner than 13 nm exhibit no structural transition down to 150 K, with a Néel (T N ) transition at ≈290 K, ≈35 K lower than thicker films. Interestingly, the T N scaling with thickness suggests realistic scaling exponents considering a critical correlation length for C‐type AFM order, rather than G‐type. The results show that finite size effects can tailor transition temperatures and modulate AFM wave modes in antiferromagnetic oxides, with implications for AFM spintronics for future information technologies.